Teasy Mobile Language: uma linguagem específica de domínio para testes funcionais em aplicativos móveis - Lima, Yury Alencar (2023)
This dissertation proposes the Teasy Mobile Language, an extension of the Teasy Framework, focusing on test automation for mobile devices. The fundamental objectives of this research are to simplify and optimize the automation process in mobile applications, filling a gap identified through systematic mapping. This systematic mapping of the literature highlighted the demand for agile and efficient solutions for mobile testing. The study takes a comprehensive approach, starting with systematic mapping to consolidate existing knowledge and identify areas of research in need of attention. Then, a case study is carried out in a real industrial environment, where the Teasy Mobile Language is empirically evaluated. The results of this case study highlight the effectiveness of the language, emphasizing benefits such as clear syntax, speed in creating test scenarios and ease of learning. Additionally, specific areas that can be improved are identified, providing valuable guidance for future developments. Final considerations emphasize the complementary role of Teasy Mobile Language in the mobile test automation ecosystem. They highlight its effective integration with the Teasy Framework, providing a cohesive experience for testers familiar with the web version of the language. Furthermore, they highlight the ongoing commitment to development, encouraged by the contribution of the community and the needs of the industry. Finally, Teasy Mobile Language emerges as a promising alternative for test automation on mobile devices, offering agility, simplicity, and effective integration in an increasingly mobile-centric scenario. Its continuous development, marked by an open source and collaborative character, promises continuous improvements to meet the growing demands of the mobile software development industry. Keywords: Functional testing, Domain-specific language, Testing automation, Software quality, Mobile applications, Software engineering.